TACI Is Required for Efficient Plasma Cell Differentiation in Response to T-Independent Type 2 Antigens - George T. Mantchev; Catarina S. Cortesão; Michelle Rebrovich; Marília Cascalho; Richard J. Bram (2007)
Abstract The control of systemic infection by encapsulated microorganisms requires T-independent type II (TI-2) Ab responses to bacterial polysaccharides. To understand how such responses evolve, we explored the function of transmembrane activator calcium modulator and cyclophilin ligand interactor (TACI), a member of the TNFR family, required for TI-2 Ab production. Quasimonoclonal (QM) mice produce robust TI-2 responses to 4-hydroxy-3-nitrophenylacetate (NP)-Ficoll, owing to the high precursor frequency of NP-specific B cells in the marginal zone of the spleen. QM mice that lack TACI produce decreased numbers of IgM (2-fold) and IgG (1.6-fold) NP-specific ASCs, compared with TACI-positive QM mice in response to immunization with NP-Ficoll. Our studies indicate that TACI acts at a remote time from activation because TACI is not necessary for activation and proliferation of B cells both in vitro and in vivo. Instead, TACI-deficient QM B cells remained in the cell cycle longer than TACI-proficient QM cells and had impaired plasma cell differentiation in response to NP-Ficoll. We conclude that TACI has dual B cell-autonomous functions, inhibiting prolonged B cell proliferation and stimulating plasma cell differentiation, thus resolving the longstanding paradox that TACI may have both B cell-inhibitory and -stimulatory functions. By promoting plasma cell differentiation earlier during clonal expansion, TACI may decrease the chances of autoantibody production by somatic hypermutation of Ig genes in response to T-independent Ags.